The Chemistry of Triazine Isomers: Structures, Reactions, Synthesis and Applications - Kushwaha, Neelottama; Sharma, C.S. (Mini Reviews in Medicinal Chemistry, 2020)
Triazine is the six-membered heterocyclic ring containing three nitrogens, which replace the carbon-hydrogen unit in the benzene ring. Based on nitrogen position present in the ring system, it is categorized in three isomeric forms, i.e., 1, 2, 3-triazine (vicinal triazine), 1, 2, 4-triazine (asymmetrical triazine or isotriazine) and 1, 3, 5-triazine (symmetrical or s-triazine or cyanidine). Triazines have a weakly basic property. Their isomers have much weaker resonance energy than benzene structure, so nucleophilic substitution reactions are more preferred than electrophilic substitution reactions. Triazine isomers and their derivatives are known to play important roles possessing various activities in medicinal and agricultural fields such as anti-cancer, antiviral, fungicidal, insecticidal, bactericidal, herbicidal, antimalarial and antimicrobial agents.
Keywords: biological activity